1994
DOI: 10.1099/00207713-44-2-223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lactobacilli from Sourdough and Description of Lactobacillus pontis sp. nov.

Abstract: The microflora of sourdough preparations was investigated by examining the physiological characteristics, whole-cell protein patterns, and 16s rRNA sequences of Lactobacillus isolates. Strains isolated from sourdough were placed in the species Lactobacillus brevis, Lactobacillus sanjkancisco, and Luctobacillus reuteri. 16s rRNA sequences were determined for L. brevis, Lactobacilluspuctivorans, Lactobacillus fermenturn, L. sanjkancisco, and L. reuteri, and oligonucleotide probes for fast specific identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
92
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 10 publications
3
92
1
3
Order By: Relevance
“…Weissella (Collins et al 1991). Whole-cell protein pattern analyses by Vogel et al (1994) have also shown the close relatedness of Lact. casei and Lact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weissella (Collins et al 1991). Whole-cell protein pattern analyses by Vogel et al (1994) have also shown the close relatedness of Lact. casei and Lact.…”
Section: Discussionmentioning
confidence: 99%
“…casei±Pediococcus group of Vandamme et al (1996) and Stiles and Holzapfel (1997). However, Collins et al (1991) and Vogel et al (1994) have clearly shown that these two species are genetically unrelated and hence belong to different lines. Metabolically, Lact.…”
Section: Discussionmentioning
confidence: 99%
“…5). The usefulness of protein fingerprinting with Coomassie blue staining has been described frequently previously (17,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Protein fingerprinting has been used successfully previously to describe Lactobacillus pontis as a new Lactobacillus species (50).…”
Section: Discussionmentioning
confidence: 99%
“…the oligonucleotide probe described as specific for L. pontis (25) is also present in the 16s rDNA sequence of Lactobacilluspanis DSM 6035T (Table 4). Despite this, the cell wall interpeptides, growth temperature, arginine cleavage, and G+C contents of strains DSM 6035T and DSM 6036 are clearly different from those of L. pontis.…”
mentioning
confidence: 99%